Emerging Infectious Diseases and COVID-19 Outbreak: Community Response to Mobility Restriction in the Early Days of Pandemic Situation in Bangladesh (Jagannath University Journal of Arts, 2026)
Bangladesh is one of the highly impacted countries of the world by the emerging infectious disease COVID-19 outbreak in 2020. As a fresh kind of disease the method of its prevention and cure even the symptoms were less discovered area and the mobility restriction protocol was imposed as the primary strategy to combat the emerging pandemic situation at least until the introduction of vaccine. This research has aimed to explore people‘s perception about COVID-19 and their behavioral response to its preventive measure in the context of Bangladesh and contribute to the literature and also future policymaking regarding infectious disease control intervention. The core research question was ―How did people perceive COVID-19 outbreak and respond to mobility restriction protocol as the primary preventive measure against its transmission? Both qualitative and quantitative data were collected through a web-based anonymous survey among the Bangladeshi general people via distribution of electronic questionnaire as google forms as well as different published literature as source of secondary data. The primary quantitative data was analysed following descriptive statistics mainly through frequency distribution and the qualitative data were analysed through thematic analysis. A total of 253 respondents took part in this research. Analysis of the data shows that without some exception respondents has basic to deep knowledge about COVID-19 as an emerging infectious disease as well as about different dimensions of mobility restrictions protocol such as lockdown, social distancing, stay home, quarantine and isolation. It is obvious that the pandemic and mobility restriction as the primary preventive measure requires a high degree of adaption and it has brought massive changes in human mobility and contact patterns.Jagannath University Journal of Arts, v-5, i-01, 2025: p131-143